The Role of Human Resources in Improving Higher Education Quality at Universitas Tangerang Raya - Endang Hermawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the role of human resources (HR) in enhancing the quality of higher education at Universitas Tangerang Raya. As a critical component of institutional development, HR comprising academic staff, administrative personnel, and university leadership plays a central role in supporting educational innovation, improving learning outcomes, and ensuring organizational effectiveness. The research employs a qualitative descriptive method to examine how HR planning, capacity building, professional training, and performance evaluation contribute to academic excellence. The findings indicate that strategic HR development at Universitas Tangerang Raya has positively influenced the quality of teaching, research productivity, and student services. Strengthening human resource capabilities, aligned with the university’s vision and mission, is essential to achieving sustainable quality improvements in higher education.